(untitled) (Journal of Engineering, 2013)
The adsorption of Cr (VI) from aqueous solution by spent tea leaves (STL) was studied at different initial Cr (VI) concentrations, adsorbent dose, pH and contact time under batch isotherm experiments The adsorption experiments were carried out at 30°C and the effects of the four parameters on chromium uptake to establish a mathematical model description percentage removal of Cr (VI). The analysis results showed that the experimental data were adequately fitted to second order polynomial model with correlation coefficients for this model was (R2 = 0.9891). The optimum operating parameters of initial Cr (VI) concentrations, adsorbent dose, pH and contact time were 50 mg/l, 0.7625 g, 3 and 100 min, respectively. At these conditions, the maximum percentage removal of Cr (VI) was 92.88%. The amounts of Cr (VI) adsorbed onto STL were highly affected by the solution pH value. Equilibrium data was modeled with Langmuir and Freundlich models isotherms. Langmuir model is found very well represent the equilibrium data with correlation factor is close to unity than the Freundlich model. The maximum monolayer adsorption capacity was found to be 47.98 mg/g at optimum conditions. The saturated adsorbent was regenerated by base treatment and found to be reuse efficiently after fourth cycle at optimum conditions as well as for safe disposal of base that contains high concentration of Cr (VI) is precipitated as barium chromate.